Next Generation PDE4 Inhibitors that Selectively Target PDE4B/D Subtypes: A Narrative Review - Andrew Blauvelt; Richard G. Langley; Kenneth B. Gordon; Jonathan I. Silverberg; Kilian Eyerich; Morten O. A. Sommer; Jakob Felding; Richard B. Warren (Adis, Springer Healthcare, 2023)
Abstract For decades, topical corticosteroids have been the mainstay of treatment for mild-to-moderate inflammatory skin diseases, even though only short-term use is approved for these agents and systemic inflammation is not addressed. Increased understanding of the immunopathogenesis of these conditions, especially for psoriasis and atopic dermatitis, has facilitated the development of antibody-based drugs that neutralize single key cytokines or their associated receptors, such as interleukin (IL)-17A/F, IL-23, and IL-17RA in psoriasis and IL-13 and IL-4Rα in atopic dermatitis. However, oral therapy is still preferred by many patients owing to the ease of use and needle-free administration. Phosphodiesterase 4 (PDE4) inhibitors have been approved for both oral and topical use for inflammatory skin diseases. In this review, we present a summary of an emerging class of selective PDE4B/D inhibitors under clinical development and compare the differences in selectivity of this new generation of PDE4 inhibitors with the less selective currently approved PDE4 inhibitors.